Aplicación de normas ISO 27005 mediante un análisis de seguridad de la información en el Departamento de la Jefatura Política del Cantón Alfredo Baquerizo Moreno (Jujan) - Pérez Laz, Carla Andreina (2020)
This case study seeks to contribute to improving the management of information security within the department of the Political Headquarters of the Canton Alfredo Baquerizo Moreno since today information is considered very important in any type of independent organization of its size and nature. These can be increasingly vulnerable, some of the causes of this problem are technological threats since these are part of the daily life of each company or organization, this causing the risk of the integrity of said information for which it is necessary an implementation of procedures through ISO 27005 standards. Within the methodology used in our search, we opted for the inductive one in order to collect the necessary information, in addition this allows us to carry out a survey that is directed to the personnel in charge of the Department of the Political Headquarters, in the results the It is very important to carry out this type of implementation of standards since in this way it improves the control of information security.